Quem conta um conto aumenta o espanto - Simões Sampaio Dias, Graciele (2019)
This study had as its aim to promote the development of the reading competence of students through practices of literary literacy in the form of workshops, using the short story as literary genre. The methodology used was the intervention research which characterizes, according to Damiani (2012), an applied research similar to Action Research that plans, implements and evaluates pedagogical practices with the objective of improving the students learning process in the study. The didactic sequence was chosen as the form for this method, since this practice provides an ample set of situations with continuity and reciprocal relations. The theoretical support was based on Dolz, Noverraz e Schneuwly (2004), Cosson (2017), Jouve (2002), Silva (2009), Zilberman (2012), among others. The locus of the research was a public school in a district of Feira de Santana. The subjects were students of an 8th grade class of the school. The instruments for the data collection were questionnaires, group studies, reading circles, testimonials and text productions. The analysis of the data revealed that the students‟ families have little influence concerning the incentive to reading, fact that leads the school and the teacher to the role of protagonists in the promotion of reading, activity that can enhance the students‟ capabilities of observation and critical thinking, helping them in the process of building themselves, as they search for new meanings and multiple comprehensions that Literature can offer.